If you help me get this right i will mark u as most brilliance!
![If you help me get this right i will mark u as most brilliance class=](https://us-static.z-dn.net/files/dee/74feeff835ae5e43d221fcb2af3699c0.png)
Answer:
f(0) = -2
f(4) = -14
f(-1) = 1
Step-by-step explanation:
f(x) = -3x-2
f(0) means let x=0
f(0) = -3(0) -2
= 0-2
= -2
f(4) means let x =4
f(4) = -3(4) -2
= -12 -2
= -14
f(-1) means let x =-1
f(-1) = -3(-1) -2
= 3 -2
= 1
Answer:
f(0) = -2
f(4) = -14
f(-1) = 1
Step-by-step explanation:
To find each answer, you substitute the number in the parentheses for x.
-3(-0) - 2 = -2
-3(4) - 2 = -14
-3(-1) - 2 = 1